2014
DOI: 10.5539/ies.v7n2p125
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Trust on Knowledge Donating and Collecting: An Examination of Malaysian Universities

Abstract: The purpose of this research is to examine the influence of affect-based trust and cognition-based trust on knowledge sharing behaviour by adopting the theory of planned behaviour in selected universities in Malaysia. The research adopted survey method and a total of 545 participants from 30 universities. Multiple regression was used to assess the research model. The findings indicate that attitude and subjective norms had positive impact on both knowledge donating and knowledge collecting. However, perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
(48 reference statements)
3
16
0
2
Order By: Relevance
“…This finding is in line with the study which was conducted by (Endres et al, 2007;Goh & Sandhu, 2014;Al-Husseini & Elbeltagi, 2014). The test on the role of knowledge donating in moderating the effect of social competence on employee performance resulted regression coefficient 0.286 with significance 0.034.…”
Section: Hypothesis Test With Moderationsupporting
confidence: 88%
“…This finding is in line with the study which was conducted by (Endres et al, 2007;Goh & Sandhu, 2014;Al-Husseini & Elbeltagi, 2014). The test on the role of knowledge donating in moderating the effect of social competence on employee performance resulted regression coefficient 0.286 with significance 0.034.…”
Section: Hypothesis Test With Moderationsupporting
confidence: 88%
“…Knowledge collecting and knowledge donating activities require intrinsic motivation. Whereas most previous research consider knowledge transfer as a single feature of knowledge sharing while and tend to ignore knowledge collecting (Goh & Sandhu, 2014). This research studies knowledge sharing as a combination of knowledge collecting and knowledge donating.…”
Section: Knowledge Sharingmentioning
confidence: 99%
“…Nevertheless, having made this statement, a majority of the relationships posited were based on the grounded¯ndings from past research. Future studies should also examine whether personal and demographic factors such as gender, ethnicity, job position, type of industry, and country of origin will a®ect PKS behaviour (Goh and Sandhu, 2014). In addition, future research could also look into the various level of analysis (i.e.…”
Section: Conclusion Discussion and Limitationsmentioning
confidence: 99%
“…This is even more apparent where studies have also showed that the existence of such high degree of trust contributes to one's willingness in sharing valuable and useful information to their counterparts (Goh and Sandhu, 2014;Zand, 1972). Consequently, an employee with higher degree of trust, will put more e®ort towards knowledge sharing, thus having a lower tendency to share pseudo knowledge with their colleagues.…”
Section: Trustmentioning
confidence: 99%
See 1 more Smart Citation